1998
DOI: 10.1016/s0169-555x(98)00023-3
|View full text |Cite
|
Sign up to set email alerts
|

The frequency and distribution of recent landslides in three montane tropical regions of Puerto Rico

Abstract: Landslides are common in steep mountainous areas of Puerto Rico where mean annual rainfall and the frequency of intense storms are high. Each year, landslides cause extensive damage to property and occasionally result in loss of life. Average population density is high, 422 peoplerkm 2 , and is increasing. This increase in population density is accompanied by growing stress on the natural environment and physical infrastructure. As a result, human populations are more vulnerable to landslide hazards. The Blanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(92 citation statements)
references
References 26 publications
(20 reference statements)
1
87
0
3
Order By: Relevance
“…In a 275 km 2 study area including the Rio Icacos watershed, landslide frequency was found to average 0.8 landslides km -2 decade -1 on forested hillslopes [43]:…”
Section: Weathering and Denudationmentioning
confidence: 99%
“…In a 275 km 2 study area including the Rio Icacos watershed, landslide frequency was found to average 0.8 landslides km -2 decade -1 on forested hillslopes [43]:…”
Section: Weathering and Denudationmentioning
confidence: 99%
“…It is known that extreme rainfalls, rapid snowmelt or seismic activities are the primary triggers of landslides (Brunetti et al, 2010;Tatard et al, 2010). Prediction of the timing of future landslide occurrence is rare, as landslide records often do not contain detailed information on the date of occurrence (Baum and Godt, 2010;Larsen and Torres-Sánchez, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Dry deposition and possibly cloudwater deposition of Hg likely shift the balance to a net Hg retention (subject to unmeasured volatilization losses), but compared to most other sites landscape retention is minimal at Icacos. One explanation could be frequent landslides (Larsen and Torres Sánchez, 1998); disturbance mobilizes THg and MeHg (Porvari et al, 2003;Munthe and Hultberg, 2004). The apparent limited Hg retention may also be an artifact of a geologic source or of Hg used in placer gold mining in this area in the late 19th and early 20th centuries (Wardsworth, 1949;Cardona, 1984).…”
mentioning
confidence: 99%